(untitled) (Ibrahim Medical College Journal, 2014)
Acute heart failure is one of the major causes of morbidity and mortality all over the world. Available published data has suggested that patients of acute heart failure with elevated level of serum cardiac troponin-I (cTn-I) have more adverse outcomes than that of acute heart failure with normal cTn-I level. Elevated level of serum cTn-I is a potential risk factor for acute heart failure. This study was carried out in the department of Biochemistry, Dhaka Medical College and National Institute of Cardiovascular Disease (NICVD) during the period from January 2010 to December 2010. In this study, 100 patients with acute heart failure were enrolled. Out of 100 cases, 50 had elevated serum cTn-I (cTn-I ? 1.0 ng/ml) and 50 had normal serum cTn-I (cTn-I < 1.0 ng/ml). The adverse outcome of the two groups were recorded and compared. Patients with high and normal serum cTn-I had mean age of 52.40 ± 8.10 years and 54.64 ± 7.26 years respectively while male and female cases were equally distributed. Left ventricular systolic dysfunction (lower ejection fraction) was significantly (p<0.05) higher among cases with elevated cTn-I level compared to those with normal level. The rate of renal failure (raised serum creatinine), impaired liver functions (raised ALT and AST) and abnormal serum electrolytes were significantly higher among the patients with elevated cTn-I compared to those with normal level. The study showed that elevated serum cTn-I level was a good biomarker to indicate adverse complications in acute heart failure cases. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20104 Ibrahim Med. Coll. J. 2013; 7(2): 32-34